Characterization of bending balloon actuators - Ko, Ung Hyun; Kumar, Vardhman; Rosen, Benjamin; Varghese, Shyni (Frontiers in Robotics and AI, 2022)
The emerging field of soft robotics often relies on soft actuators powered by pressurized fluids to obtain a variety of movements. Strategic incorporation of soft actuators can greatly increase the degree of freedom of soft robots thereby bestowing them with a range of movements. Balloon actuators are extensively used to achieve various motions such as bending, twisting, and expanding. A detailed understanding of how material properties and architectural designs of balloon actuators influence their motions will greatly enable the application of these soft actuators. In this study, we developed a framework involving experimental and theoretical analyses, including computational analysis, delineating material and geometrical parameters of balloon actuators to their bending motions. Furthermore, we provide a simple analytical model to predict and control the degree of bending of these actuators. The described analytical tool could be used to predict the actuating function of balloon actuators and thereby help generate optimal actuators for functions which require control over the extent and direction of actuation.